A scoping review of interventions on middle school students’ attitudes towards science - Noé Manuel García-Pérez; Gonzalo Peñaloza (PLoS ONE, 2025)
The aim of the study was to review the scientific literature on educational interventions to promote positive attitudes towards science in middle school students. Due to the decline in positive attitudes towards science observed in this critical age group of students and the implementation of training programmes aimed at changing this situation, we sought to identify components of training proposals that have received attention from researchers. This paper presents a scoping review of 37 papers published in English and Spanish over the last 10 years. The review aims to describe the research outputs and analyse the effectiveness and characteristics of program interventions, drawing from various databases. The results show the need to examine the operational definition of the constructs used in the programmes, to focus attention on the influence of intrinsic variables on middle school students’ attitudes towards science, such as racial group or self-efficacy, and to conduct follow-up evaluations to assess the permanence of attitudes. While acknowledging limitations related to construct clarity or language restrictions in the search process the findings suggest that middle school students’ attitudes towards science remain an open area of research, as there is no consensus on the characteristics of effective programmes.